STUDI KOMPARASI PENGATURAN PEMBUKTIAN PERKARA PIDANA BERDASARKAN SISTEM HUKUM INDONESIA DAN KOREA SELATAN - Khairani Catika Juliana; Gandes Candra kirana (Reformasi Hukum Trisakti, 2023)
Proof is a crucial element in resolving legal issues, undertaken based on the will or desire of the parties involved. Recognizing that Indonesia and South Korea have similar legal systems, there may be differences in their legal regulations, especially regarding the proof of criminal cases. The research problem formulation is: What are the differences and similarities in proving criminal cases in Indonesia and South Korea? And what are the weaknesses and strengths of proving criminal cases in Indonesia and South Korea? The aim of this research is to understand and describe the differences, similarities, weaknesses, and strengths of proving criminal cases in Indonesia and South Korea. This study uses a Comparative method, conducted through a legal comparison between one legal system and another. The research adopts a normative research type, utilizing literature review to describe the research problem. The findings indicate that despite significant differences in the types of evidence between Indonesia and South Korea, they have nearly identical legal systems and share similar strengths and weaknesses. However, in some aspects, Indonesia can adopt certain elements from the South Korean legal system.